(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Epidemiological procedure, clinical-specific brucellosis in physiological and excretory criteria and prognostic criteria. In the analyzed morbidity, patients and 94 hot tubes (form No. 003 / y) with impedance were studied, guarantee rejection, an infectious disease, rotting and characteristic, severe brucellosis.